The Management and Outcomes of Placenta Accreta, Increta, and Percreta in the United Kingdom: A Population-based Descriptive Study. Issue 1 (March 2015) - Fitzpatrick, K.E.; Sellers, S.; Spark, P.; Kurinczuk, J.J.; Brocklehurst, P.; Knight, M.
Abstract : ( BJOG . 2014;121(1):62–70)